The Cultural Underpinnings of English: An Analysis of the Epistemic Phrase “I Think” and Related Models and their Translation into Lithuanian - Tumosaitė, Aušra; Grigaliūnienė, Jonė (Vertimo studijos, 2017)
[full article and abstract in Lithuanian; abstract in English]The present paper deals with the analysis of the English epistemic phrase “I think” and its related models and their translation into Lithuanian. The aim of the paper is to find out whether the phrase “I think”and its related models can be treated as a cultural concept, peculiar to just the English language, having a unique Anglo script which does not have an exact equivalent in other languages. The analysis is based on  the  methodological  framework  of  the  Natural  Semantic  Metalanguage  and  the  concept  of  cultural  scripts worked out by Anna Wierzbicka.The data comes from two parallel corpora: the Parallel Opus Corpus, which stores texts of European Parliament meetings, and the Parallel English-Lithuanian Corpus compiled  at  the  Centre  of  Computational  Linguistics  of  Vytautas  Magnus  University  (PELC),  which  consists mainly of fiction and some non-fiction texts. The analysis identified the most frequent transla-tion  variants  in  the  spoken  and  written  language.  It  has  been  discovered  that  in  the  spoken  language  (Opus Corpus), the most frequent translation variant of the epistemic phrase “I think” is the first-person present-tense mental perception verb manau (53,5per cent). Manau cultural script corresponds to the Anglo “I think” script. Meanwhile, in the written language (PELC), manau constitutes 26,5percent of all “I think” translation variants. In the remaining cases the translation of the epistemic phrase “I think” varied highly. The findings show that the related epistemic phrases  “I believe”, “I suspect”, “I suppose” and “I guess” in most cases are also rendered by means of the first-person present-tense mental perception verb manau. The research showed that epistemic phrases are cultural concepts that have no direct equiva-lents in the Lithuanian language and that the cultures and mindsets in question are different. It has been established that cultural acknowledgement of the limitations of one’s knowledge is a vast topic of Anglo culture and the English language and it should be approached carefully and systematically.
Keywords: none